SAT0070 Baricitinib versus adalimumab in patients with active rheumatoid arthritis: analysis of patients achieving a moderate eular response at week 4. (15th June 2017) - Kvien, TK; Riel, P van; Rubbert-Roth, A; Blanco, R; Liu-Leage, SS; Larsson, E; Lund, H; Lόpez-Romero, P; Zaremba-Pechmann, L; Emery, P
Abstract : Background: Baricitinib (BARI) is a selective inhibitor of Janus kinase, 1 improves disease activity in patients (pts) with rheumatoid arthritis (RA), and is associated with inhibition of structural joint damage. 2–4 Response to BARI observed at week (wk) 4 may be useful to predict future response. 5 Objectives: To characterise pts with RA who achieved moderate EULAR responses (MERs) 6 at wk 4 and to describe the outcomes through wk 52 while continuing the assigned treatment. Methods: Pts enrolled in the RA-BEAM study with active RA who had an inadequate response to methotrexate (MTX) were randomised 3:3:2 to placebo (PBO), BARI 4 mg once daily, or adalimumab (ADA) 40 mg biweekly. 1 Pts who showed good or no EULAR responses at wk 4 were excluded. For the MER cohort, the cumulative incidence for first transition to good EULAR response and to no EULAR response from wk 4 through wk 52 was estimated in the presence of competing risks events, which either hinder observation of the events of interest or modify the chance that these events occur. 7 Pts who transitioned from MER to no EULAR response or pts who were rescued or discontinued because of an adverse event or lack of efficacy were counted as no EULAR response; pts who discontinued the study for other reasons (eg, lost to follow-up, death) were censored at the time of discontinuation. No formal statistical tests were performed for these post hoc analyses. Results: Of 1305 pts who received at least 1 dose of study drug, 683 experienced MERs at wk 4, including 37.3% (182/488), 62.0% (302/487), and 60.3% (199/330) of pts on PBO, BARI, and ADA, respectively. Pts who achieved MERs at wk 4 on BARI and ADA had similar baseline disease activity characteristics (Table 1 ). The mean age of the MER subgroup was 53 years, and the mean disease duration was 8.7 years. The mean MTX dosage was 15 mg/wk, and 59% of pts were taking concomitant oral glucocorticoids. At wk 4, 27% (131/487) and 11% (54/487) of pts on BARI vs 29% (95/330) and 11% (36/330) of pts on ADA experienced no response or good response, respectively. The cumulative incidence for the first transitions to good EULAR response at wks 12, 24, and 52 was higher in pts who reached MERs at wk 4 on BARI than those on ADA. The cumulative incidence for the first transitions to subsequent no EULAR response was higher in pts who achieved MER at wk 4 on ADA (Figures 1A and 1B, Table 2) than those on BARI. Conclusions: Among pts achieving early MER on BARI and ADA, subsequent loss of response was less common for pts on BARI than for those on ADA. Transitions to good EULAR response were more common for pts who achieved MERs on BARI than for those on ADA. Mechanistic explanations warrant future study. References: Taylor et el. 2015 ACR Meeting. Abstract 2L. Dougados M, et al. Ann Rheum Dis. 29 Sep 2016. Smolen et al. Ann Rheum Dis. 31 Oct 2016. Fleischmann R et al. Arthritis Rheumatol. 09 Oct 2016. Kremer et al. 2015 ACR Meeting. Abstract 1050. Gestel et al. Arthritis Rheum 1996. Lin G et al. SAS Global Forum 2012. Acknowledgements: Inmaculada de la Torre MD, PhD, Senior Medical Advisor, contributed to this abstract. Disclosure of Interest: T. K. Kvien Consultant for: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celltrion, Eli Lilly, Epirus, Janssen, Merck-Serono, MSD, Mundipharma, Novartis, Oktal, Orion Pharma, Hospira/Pfizer, Roche, Sandoz, and UCB, Speakers bureau: AbbVie, Biogen, BMS, Boehringer Ingelheim, Celltrion, Eli Lilly, Epirus, Janssen, Merck-Serono, MSD, Mundipharma, Novartis, Oktal, Orion Pharma, Hospira/Pfizer, Roche, Sandoz, and UCB, P. van Riel Consultant for: Eli Lilly and Company, A. Rubbert-Roth Consultant for: Eli Lilly and Company, R. Blanco Consultant for: Eli Lilly and Company, S. S. Liu-Leage Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, E. Larsson Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, H. Lund Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, P. Lόpez-Romero Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, L. Zaremba-Pechmann Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, P. Emery Consultant for: Pfizer, MSD, Abbvie, BMS, UCB, Roche, Novartis, Samsung, Sandoz, Eli Lilly and Company